جهود الشيخ عبد العزيز الشريف السّوفي في المقاومة الثقافية للاستعمار الفرنسي - غمام عمارة, أحمد (University of Eloued جامعة الوادي, 2022)
ساهم العلاّمة عبد العزيز الشريف بقسط وافر في إبراز عظمة هذه الأمة ومجدها التليد، والدفاع عن مقومات أمّته العربية، وشخصيتها الإسلامية، وتعليم النشء قواعد اللغة العربية الصحيحة، وبذل عطاءات في سبيل إحداث نهضة علمية، وفكرية رائدة، للمحافظة على شخصية المجتمع من التفسخ والذوبان، حتى يواكب التطورات المستجدة التي برزت في العالم الأوربي المتمدّن، فمن هو العلاّمة عبد العزيز الشريف؟ وما هي أبرز جهوده في المقاومة الثقافية للمستعمر الفرنساوي؟ حاولت هذه الدراسة أن تميط اللثام عن هاته الشخصية، وتعيد الاعتبار للشيخ عبد العزيز الشريف، وتثبت أنه عالم من علماء "وادي سوف" ضرب بحظ وافر في حماية بلده خصوصا، ووطنه الجزائر عموما، بما قام به من إنجازات. وتوصي الدراسة الطلبة، والباحثين في الدراسات الأكاديمية على اختلاف تخصصاتها؛ الشرعية، أو الأدبية، أو التاريخية أن يتولّوا التعريف بعلماء منطقة وادي سوف، ودورهم في خدمة أمّتهم، ووطنهم. Abstract: The mark Abdul Aziz Al-Sharif contributed a great deal to highlight the greatness of this nation and its glory, defend the elements of his Arab nation, its Islamic personality, teach young people the correct Arabic grammar, and make tenders for the creation of a pioneering scientific and intellectual renaissance, to preserve the personality of society from disintegration and melting, in order to keep pace with the new developments that have emerged in the civilized European world, who is the mark Abdul Aziz Al-Sharif? What are his most prominent efforts in the cultural resistance of the French colonist? This study tried to reveal this personality, restore consideration to Sheikh Abdelaziz Al-Sharif, and prove that he is a scholar of the 'Wadi Souf' who was struck with great luck in protecting his country in particular, and his homeland Algeria in general, with his achievements.\r\nThe study recommends that students and researchers in academic studies of all disciplines; legal, literary or historical, be introduced to the scholars of the Wadi Souf region, and their role in serving their nation and their homeland.
Efforts of Sheikh Abdul Aziz Al-Sharif al-Soufi\r\nIn the cultural resistance to French colonialism\r\n
مداخلة
Keywords: عبد العزيز الشريف؛ وادي سوف؛ الاستعمار الفرنسي؛ الزاوية؛ الإصلاح; Abdelaziz Cherif; Wadi Souf; French colonialism; Zawiya; Reform